Manajemen Pra Tsunami - Fatkhul Rizqi, Khoirul; Sutarto, Sutarto; Ismunandar, Helmi (CV. Jasa Sukses Abadi, 2024)
Geographically, Indonesia is in the tectonic ring, where 3 tectonic plates meet, including the Indo-Austalian Plate, the Eurasian Plate and the Pacific Plate. The meeting of these 3 plates carries the risk of an underwater earthquake causing a tsunami. Tsunamis are a threat to residential areas in coastal areas. This is the biggest problem for coastal communities because it can cause a lot of casualties and very serious damage to buildings. The largest tsunami that occurred in Indonesia was a tsunami measuring 9.3 SR (Ritcher Scale) in Aceh Province on December 26 2004, which resulted in many fatalities. This article aims to understand and describe pre-tsunami management. This article uses a qualitative approach with discussion using paragraph descriptions of the data. The results of this article explain that there are several efforts that can be made to minimize tsunamis, namely pre-tsunami management consisting of mitigation, preparedness and early detection. According to Law no. 24 of 2007, Disaster management is a dynamic, continuous and integrated process that aims to improve the quality of things related to disaster analysis and observation as well as steps for prevention, mitigation, preparedness, early warning, emergency management, disaster rehabilitation and reconstruction. . Therefore, pre-tsunami management is very important for all communities, especially communities living in areas close to the sea such as beaches and ports.